ANALISIS SOAL PADA BUKU IPAS KELAS IV DI SD MUHAMMADIYAH PURWODADI BERDASARKAN HIGHER ORDER THINKING SKILLS (HOTS) TAKSONOMI BLOOM - Dwirex Cece Jihan; Ashari; Muflikhul Khaq (Jurnal Binagogik, 2024)
This research aims to find out the results of the analysis of science material competency test questions in the Class IV Science Book at Muhammadiyah Purwodadi Elementary School based on Bloom's Higher Order Thinking Skills (HOTS) Taxonomy. The type of research in this research is qualitative descriptive research. The subject of this research is a Companion to the Main Textbook for Learning Natural and Social Sciences for Class IV Elementary and MI for the 2022/2023 Academic Year written by Much. Azam and published by PT Tiga Serangkai Pustaka Mandiri in 2022. Data was collected using interviews, document analysis and documentation. The data in this study were analyzed using the Miles and Huberman data analysis technique with 4 steps, namely data collection, data reduction, data presentation, and drawing conclusions. The results of this analysis show that the HOTS category questions included in the competency test are still small. The total number of questions analyzed was 135 questions and only 24 questions were in the HOTS category with a percentage of 17.8% and the other 111 questions with a percentage of 82.2% were in the LOTS question category. The explanation of the questions consists of remembering (C1) with 35 questions, understanding (C2) with 51 questions, applying (C3) with 25 questions, and analyzing (C4) with 24 questions. The HOTS questions in the science material competency test only contain questions at the analyzing level (C4) and do not contain questions at the evaluating (C5) and creating (C6) levels.